PERAN MASYARAKAT DALAM PERENCANAAN DAN PELAKSANAAN PEMELIHARAAN JALAN - Sekaryadi, Yudi (Jurnal HPJI (Himpunan Pengembangan Jalan Indonesia), 2025)
Abstract This study was conducted in Sidamulya Village, Jalaksana District, Kuningan Regency, in West Java Province. Sidamulya village is traversed by the Cirebon–Kuningan provincial road which is in good and moderate condition, the Jalaksana–Simpang Pejambon district road which is in moderate condition and slightly damaged, and several village roads are in moderate condition, lightly damaged, and heavily damaged. The road maintenance program in the Sidamulya Village environment is implemented based on the results of road condition surveys. Maintenance of the Cirebon-Kuningan Road Section is proposed using a routine maintenance program, while maintenance of the Jalaksana-Simpang Pejambon Road Section is proposed using a periodic maintenance program. Meanwhile, maintenance of village roads is proposed with a periodic maintenance and rehabilitation program. Implementation of road maintenance can be carried out by including village community participation through the Type IV self-management method, where planning is carried out by the government or community, while implementation and supervision are carried out by the community. The types of work that can be done by village communities are simple jobs and do not require high-tech equipment. Keywords: road conditions; community participation; road maintenance; road planning; self-management Abstrak Studi ini dilakukan di Desa Sidamulya, Kecamatan Jalaksana, Kabupaten Kuningan, di Provinsi Jawa Barat. Desa Sidamulya dilewati oleh jalan provinsi Cirebon–Kuningan yang berkondisi baik dan sedang, jalan kabupaten Jalaksana–Simpang Pejambon yang berkondisi sedang dan rusak ringan, dan beberapa jalan desa berkondisi sedang, rusak ringan, dan rusak berat. Program pemeliharaan jalan di lingkungan Desa Sidamulya dilaksanakan berdasarkan hasil survei kondisi jalan. Pemeliharaan ruas jalan Cirebon–Kuningan diusulkan menggunakan program pemeliharaan rutin, sedangkan pemeliharaan ruas jalan Jalaksana– Simpang Pejambon diusulkan dengan program pemeliharaan berkala. Sementara itu, pemeliharaan jalan desa diusulkan dengan program pemeliharaan berkala dan rehabilitasi. Pelaksanaan pemeliharaan jalan dapat dilakukan dengan me-nyertakan partisipasi masyarakat desa melalui metode swakelola Tipe IV, yang mana perencanaan dilakukan oleh pemerintah atau masyarakat, sedangkan pelaksanaan dan pengawasan dilakukan oleh masyarakat. Jenis pekerjaan yang dapat dilakukan oleh masyarakat desa adalah pekerjaan yang sederhana dan tidak memerlukan peralatan berteknologi tinggi. Kata-kata kunci: kondisi jalan; partisipasi masyarakat; pemeliharaan jalan; perencanaan jalan; swakelola